A Computational Enhancement Of Base64 Algorithm Using Residue Number System Algorithms - Logunleko, Kolawole Bariu; Logunleko, Abolore Muhamin; Wuraola, Asaju-Gbolagade Ayisat; Babatunde, Akinbowale Nathaniel; Gbolagade, Kazeem Alagbe (PT. Lontara Digitech Indonesia, 2025)
A significant part of information security has been played by cryptography techniques. Today's daily existence depends heavily on the advancement of data, information, and communication technologies. Consequently, there is a huge increase in the need for data and information. In communicating data over a public network, data security is a necessity that must be carefully taken into consideration. Thus, Base64 algorithm has been used in numerous security applications for ensuring data confidentiality, integrity and authentication. However, research shows that there is security vulnerabilities in most widely used Base64 algorithm due to the absence of key mechanism. To address this concern, this research employs residue number system algorithms for the enhancement of base64 algorithm because of its cryptographic features whereby strengthen the transformation of the existing base64 algorithm to produce a novel symmetric-based cryptographic algorithm. The developed algorithm generates a symmetric key by shuffling the original key with the textual data, making the transformation of each character of the data better each time it is shuffled. Therefore, the research bridges the security gap in Base64 cryptographic algorithm by factoring key mechanism of RNS based algorithm into the newly developed algorithm. In addition, the developed symmetric-based cryptographic algorithm is more robust than the existing Base64 cryptographic algorithm because of the planned pattern and confusion produced during the methodology procedure thereby safeguards the data more effectively as shown in the cipher text generated.